THE INFLUENCE OF YOUTH’ UNDERSTANDING OF DRUGS TOWARDS ITS ABUSE IN THE INDONESIA-PAPUA NEW GUINEA BORDER - Hardy, Syaifoel; Tukayo, Isak Jurun Hans; Saljan, Mohammad (Journal of Islamic Nursing, 2021)
A lack of understanding about drugs can have a big impact on adolescents in the border area between Indonesia and Papua New Guinea (PNG) which is known to be prone to drug transactions.This study analyzed the influence of the adolescents’ understanding in the border area of Indonesia-PNG on drug abuse and offers a solution from the perspective of Community Health Nursing. Quantitative, comparative study with cross-sectional design. The population was high school students in 4 cities (Jayapura, Boven Diegol, Keerom, and Merauke). The sampling technique was non-probability sampling with a sample size of 230 respondents. The data collection tool used a questionnaire of Guttmann and Likert scale based on Bloom's Taxonomy Theory. Data were analyzed using the SPSS application (Statistical Package for Social Sciences) Version 25 to see the differences between adolescents who understood drugs and those who did not. Low knowledge of adolescents about drug information has an effect on unfavorable attitudes by 54.6%. While the high knowledge of adolescents about drugs, the effect of a good attitude was 58.6%. This study projected adolescents' high knowledge about drugs would result in a good attitude i.e. they could avoid drug abuse. Keywords: Drugs, adolescents, community nursing.